Social media governance: can social media companies motivate voluntary rule following behavior among their users? - Tyler, Tom R. (Journal of experimental criminology, 2021)
Objectives The purpose of these studies is to examine whether the procedural justice of a social media platform enforcement system for content moderation shapes offenders' post-message takedown recidivism rates. Methods Users whose posts have been removed from the platform (taken down) for rule violations evaluate the justice of the platform enforcement procedure. The impact of those evaluations upon subsequent rule violations is measured. In addition, in study 2, users are randomly assigned to receive a message emphasizing the procedural justice of platform procedures and the impact of that message upon subsequent rule violations is assessed. Results In both studies, users who indicate that the procedures involved in the removal of their post have been fair are less likely to post new violating content in the future. In addition, those users who receive a message emphasizing the procedural justice of the platform’s mechanisms of enforcement are less likely to post new violating content in the future in comparison to those users randomly chosen to be no-message controls. Conclusions Social media platforms are under government and public pressure to regulate the content of the posts that appear on their sites. One enforcement strategy that has been found to be effective in legal settings is to encourage self-regulation through procedural-justice-based approaches to rule enforcement. This paper tests the viability of extending these approaches to social media platforms. Results of both studies suggest that a strategy of encouraging self-regulation by the use of procedures that users rate as being just can successfully lower recidivism rates in a social media setting.